Improving the separation of chalcopyrite and galena by surface oxidation using hydroxyethyl cellulose as depressant. (1st January 2021) - Feng, Bo; Jiao, Xiangke; Wang, Huihui; Peng, Jinxiu; Yang, Guang
Highlights: A large amount of H2 O2 or HEC can depress galena selectively. The combined use of H2 O2 and HEC can decrease the reagent concentration greatly. HEC adsorbed on galena surface through chemical reaction with the oxidation products. The addition of H2 O2 can generate more oxidation products. Abstract: The role of hydrogen peroxide (H2 O2 ) and hydroxyethyl cellulose (HEC) in the flotation separation of chalcopyrite and galena has been investigated and the reason why H2 O2 can enhance the depression effect of HEC has been explained. The results show that either H2 O2 or HEC can depress galena selectively, but the reagent concentration needed is large. A small amount of HEC can completely depress the flotation of galena in the presence of H2 O2, but had a little effect on chalcopyrite flotation at the same condition. Therefore, the combined use of H2 O2 and HEC can achieve the flotation separation of galena and chalcopyrite. HEC adsorbed on galena surface mainly by chemical reaction with the oxidation products that were generated on galena surface and the addition of H2 O2 can generate more oxidation products, which significantly improves the adsorption of HEC.